THE EFFECT OF THE EFFECTIVENESS OF GREATDAY ATTENDANCE IMPLEMENTATION AND WORK ENVIRONMENT ON EMPLOYEE WORK DISCIPLINE AT XYZ SCHOOL, BEKASI CITY - Patimatus Jariyah; Zaharuddin; Dudun Junaedi (Journal Informatic, Education and Management (JIEM), 2026)
The Effect of the Effectiveness of GreatDay Attendance Implementation and Work Environment on Employee Work Discipline at XYZ School, Bekasi City. Employee work discipline is one of the key factors in improving organizational performance and productivity, particularly in educational institutions. In the digitalization era, the implementation of digital attendance systems such as GreatDay is expected to improve the effectiveness of attendance management and encourage employee discipline. However, the effectiveness of implementing the digital attendance system still faces various challenges, while the work environment is also presumed to influence employees' level of discipline. This study aims to analyze the effect of the effectiveness of GreatDay attendance implementation and the work environment on employee work discipline at XYZ School, Bekasi City. This study used a quantitative approach with descriptive and verificative methods. The research population consisted of all employees at XYZ School, Bekasi City, totaling 75 people. The sampling technique used was saturated sampling; therefore, the entire population was used as the research sample. Data were collected through questionnaires using a 1-5 Likert scale distributed to 75 respondents. Data analysis techniques employed multiple linear regression analysis using SPSS version 25, including classical assumption tests (normality, multicollinearity, heteroscedasticity), t-test (partial), F-test (simultaneous), and coefficient of determination (R²). The results show that: (1) the Effectiveness of GreatDay Attendance Implementation has a partial and significant effect on Employee Work Discipline with a significance value of 0.000 < 0.05 and a coefficient of determination of 15.9%; (2) Work Environment has a partial and significant effect on Employee Work Discipline with a significance value of 0.004 < 0.05 and a coefficient of determination of 11.1%; (3) the Effectiveness of GreatDay Attendance Implementation and Work Environment simultaneously have a significant effect on Employee Work Discipline with a significance value of 0.000 < 0.05 and a coefficient of determination of 42.3%. This indicates that both independent variables together explain 42.3% of the variation in employee work discipline, while the remaining 57.7% is influenced by other variables outside this study. Based on these findings, it can be concluded that the effectiveness of GreatDay attendance implementation and the work environment significantly affect employee work discipline, both partially and simultaneously. Therefore, XYZ School, Bekasi City, is advised to improve the effectiveness of GreatDay attendance implementation through more intensive training, improved technological infrastructure, and systematic monitoring and evaluation, as well as to create a conducive work environment by enhancing the workplace atmosphere, harmonizing inter-employee relationships, and providing adequate work facilities to improve employee work discipline.